Physics at Lower Secondary Schools: Comparison between the Czech Republic, Estonia, Poland and Slovenia - Kácovský, Petr; Koudelková, Věra; Snětinová, Marie (Scientia in educatione, 2019)
Results of the worldwide PISA study in science performance from past years (2009, 2012 and 2015) show that Czech pupils are placed in the OECD average, whereas some countries with similar cultural and historical background are statistically significantly above it as well as above the results of the Czech Republic. As an example, Estonia, Poland and Slovenia belong to these countries and therefore they were chosen for the presented comparative study. The study focuses on comparison of national curricula of these countries, especially on fundamental aspects important for physics education at lower secondary schools. The study highlights the comparison of teaching content and learning outcomes in physics, interdisciplinary education and cross-curricula subjects, educational methods and assessment and field-specific key competences. One of the most evident differences that this study has detected is in the level of autonomy that the curricular documents give schools in deciding what the learning process will look like. This result as well as other findings will be discussed in the paper.